Pengaruh Perceived Usefulness, Perceived Ease of Use, dan Social Influence Terhadap Continuance Intention Aplikasi Linkaja - Tegar Hanafi; Diena Noviarini; Fauzan Fadlullah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to analyze the influence of perceived usefulness, perceived ease of use, and social influence on the continuance intention of the LinkAja application, both partially and simultaneously. This study employs a quantitative approach with a survey method and Structural Equation Modeling based on Partial Least Squares (SEM-PLS) as the analysis technique. The sample in this research consists of 255 respondents residing in the DKI Jakarta area , selected through a purposive sampling technique. Data were analyzed using SmartPLS 4.0 software. The results of the analysis indicate that: (1) Perceived usefulness has a positive and significant effect on the continuance intention of the LinkAja application. (2) Perceived ease of use has a positive and significant effect on the continuance intention of the LinkAja application. (3) Social influence has a positive and significant effect on the continuance intention of the LinkAja application. These findings confirm that social influence is the most dominant factor in influencing user continuance intention. Therefore, application developers need to integrate the usefulness of features, an intuitive interface, and the strengthening of the community base to maintain user loyalty in the competitive digital wallet market.